Safety and efficacy of Gamma Knife radiosurgery in hypothalamic hamartomas with severe epilepsies: A prospective trial in 48 patients and review of the literature. (7th June 2017) - Régis, Jean; Lagmari, Medhi; Carron, Romain; Hayashi, Motohiro; McGonigal, Aileen; Daquin, Géraldine; Villeneuve, Nathalie; Laguitton, Virginie; Bartolomei, Fabrice; Chauvel, Patrick
Summary: Epilepsies associated with hypothalamic hamartomas (HHs) are frequently drug resistant with severe psychiatric and cognitive comorbidities. We performed a prospective trial to evaluate the safety and efficacy of Gamma Knife radiosurgery (GKS). Between October 1999 and October 2007, a total of 57 patients were investigated, included and treated by GKS in Timone University Hospital. Preoperative workup and 3‐year postoperative evaluation consisted of seizure diary, neuropsychological, psychiatric, endocrinologic, visual field, and visual acuity examinations. Follow‐up of >3 years was available for 48 patients. Topologic type was type I in 11 patients, type II in 15, type III in 17, type IV in one, type V in one, type VI in one, and mixed type in 2. The median marginal dose was 17 Gy (min 14 and max 25 Gy). The median target volume was 398 mm 3 (28–1, 600 mm 3 ). Due to partial results, 28 patients (58.3%) required a second treatment. The median follow‐up was 71 months (36–153 months). At last follow‐up, the rate of Engel class I outcome was 39.6%, Engel class II was 29.2% (I+II 68.8%), and Engel class III was 20%. Global psychiatric comorbidity was considered cured in 28%, improved in 56%, stable in 8%, and continued to worsen in 8%. No permanent neurologic side effect was reported (in particular, no memory deficit). Nondisabling transient poikilothermia was observed in three patients (6.2%). A transient increase of seizure frequency was reported in 8 patients (16.6%) with a median duration of 30 days (9–90 days). Microsurgery was proposed because of insufficient efficacy of GKS in seven patients (14.5%) with a postoperative Engel class I–II in 28.6%. This prospective trial demonstrates very good long‐term safety and efficacy of GKS for 2 patients. Beyond seizure reduction, the improvement of psychiatric and cognitive comorbidities along with better school performance and social functioning, being better socially integrated, having friends having a social life, working, participating to group activities turn out to be major benefits of GKS in this group of patients with frequently catastrophic epilepsy.